Translation Norms Of Cultural References From Arabic Into English In The Queue: An Analysis Using Newmark’s Cultural References And Toury’s Operational Norms - Alharahsheh, Abdelrauof Meqbel Ah (2024)
The present study is primarily about the translation norms of cultural references from Arabic into English in Basma Abdelaziz's novel, The Queue. This particular novel was selected for analysis because it abounds with cultural references that mirror cultural values. To achieve its objectives, the study adopts two translation theories: Toury's (2012) framework on translation norms and Newmark's (1988) categorizations of cultural expressions. It delves into the functions of initial and preliminary norms, as well as the application of operational norms in the translation of The Queue novel into English, utilizing Toury's (2012) theory of translation norms. The study aims to achieve the following objectives: firstly, to delineate the function of preliminary and initial norms at a macro level. Secondly, to scrutinize the micro-level operational norms concerning textual linguistics and translation shifts in the process of rendering Arabic cultural references into English. These translation shifts are indicative of the translator's personal perspective on source language norms and the adherence to the linguistic and cultural norms prevailing in the target language context. The study revealed that there are macro-level distinctions between the source and target texts, stemming from cultural differences between Arabic and English. Furthermore, the study illustrates that the translator of The Queue faced challenges in effectively transferring cultural references to the target text, leading to certain discrepancies at the micro-level.